HUBUNGAN ANTARA TINGKAT PENGETAHUAN MAHASISWA DENGAN SIKAP PENGELOLAAN SAMPAH DI FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Dewi Latifah; Suyanto "; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTWaste management is an activity in waste reduction and handling that is systematic, continous and thorough. The state of good and health environmental in acollege is needed as carrying comfort in learning. The state of a clean and healthy environment is determined by the behavior of individuals who materialized in the form of knowledge, attitudes and actions. The purpose of this study to determine the correlation between knowledge level of student with attitudes of waste management in Medical Faculty of Riau University . This type of research was analytic survey with cross sectional approach. Samples in this reseacrh were 90 respondents from population students of Medical Faculty of Riau University.The data that were collected using a questionnaire to assess knowledge and attitudes. The results of this study, obtained that 44 students (48,9%) had a good knowledge and 65 students (72,2%) had a neutral stance. From the statistical test result was obtained that p=0,971 for the correlation with the students knowledge of waste management attitude.Keywords: Knowledge, attitudes, waste management